Sedimentary and tectonic setting of a mass-transport slope deposit in the Halifax Group, Halifax Peninsula, Nova Scotia, Canada - Waldron, John W.F.; Jamieson, Rebecca A.; Pothier, Hayley D.; White, Chris E. (Atlantic Geoscience, 2015)
Fine-grained metasedimentary rocks of the Halifax Group in southern mainland Nova Scotia can be subdivided into mappable units. In Halifax Peninsula, sulphide-rich hornfels, black slate, metasiltstone, and metasandstone of the Cunard Formation are overlain by grey metasedimentary rocks with abundant cross-laminations and local carbonate and calc-silicate concretions, assigned to the Bluestone Quarry Formation. No fossils are known from the Bluestone Quarry Formation but lithological correlatives elsewhere are Tremadocian. The Bluestone Quarry Formation is here divided into four members. The lowest (Point Pleasant member) contains thin parallel-laminated and cross-laminated metasandstone beds with Bouma Tbcde and Tcde structures, and thicker beds with Bouma ‘a’ divisions. The Black Rock Beach member lacks the thicker massive beds and is dominated by rippled and cross-laminated metasedimentary rocks. The overlying Chain Rock member, an erosion-resistant ridge-forming unit, is disrupted by folds and boudinage. Bedding is truncated at the upper contact, and the internal structures are overprinted by (and therefore predate) the Neoacadian cleavage. They are interpreted as products of synsedimentary mass transport. Scarce folds in the Chain Rock member and current ripples in the underlying unit are consistent with a N or NW transport direction. The overlying Quarry Pond member consists of thinly bedded coherent metasedimentary rocks that generally resemble those of the Black Rock Beach member. Although there are indications of upward shallowing in equivalent successions elsewhere in the Halifax Group, the presence of a major mass transport deposit in the Bluestone Quarry Formation shows that this part of the Halifax Group was deposited on a submarine paleoslope. The failure of geologists to identify this feature in much-visited outcrops testifies to the difficulty of identifying synsedimentary deformation features that have been overprinted by later tectonic deformation.